Development of an Antibacterial Root Canal Filling System Containing MDPB. (December 2014) - Kitagawa, R.; Kitagawa, H.; Izutani, N.; Hirose, N.; Hayashi, M.; Imazato, S.
An antibacterial monomer 12-methacryloyloxydodecylpyridinum bromide (MDPB)-containing experimental, chemically cured primer was prepared to develop a new resin-based root canal filling system. This study investigated the antibacterial effects of the MDPB-containing primer (experimental primer [EP]) against Enterococcus faecalis and assessed the in vitro bonding and sealing abilities of the filling system, consisting of EP and a Bis-GMA-based sealer resin. Antibacterial effects of EP were evaluated by contact with planktonic or adherent bacteria for 30 or 60 sec, and the viable bacterial number was counted. The antibacterial effects against E. faecalis in dentinal tubules were also assessed, according to a root canal infection model. Bonding and sealing abilities of the experimental filling system were examined by microtensile bond strength tests and leakage tests based on fluid filtration methods. Significantly greater reduction in viable bacteria in planktonic and adherent form was obtained by short-period contact with EP compared with the control primer (without MDPB) or with the proprietary (Epiphany) primer ( p < .05). Significantly greater bactericidal effects of the EP inside the dentinal tubule of root, as opposed to the control primer or Epiphany primer, were confirmed according to a root canal infection model ( p < .05), and 100% killing of E. faecalis could be obtained by the application of EP after irrigation with a 5% sodium hypochlorite solution. The experimental endodontic filling system demonstrated significantly greater bond strength to root dentin than Epiphany sealer system (Epiphany primer and Epiphany Root Canal Sealant; p < .05), showing formation of resin tags and a hybridized layer. Leakage tests clarified that the experimental system provided excellent sealing. This study confirmed that the MDPB-containing experimental antibacterial primer has the ability to effectively disinfect the root canal. Additionally, the experimental root canal filling system employing this primer and the Bis-GMA-based sealer resin is useful for achieving good sealing, suggesting its possible benefit for successful endodontic treatments.